2000
DOI: 10.1021/ol006449e
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Allyl Transfers Utilizing Soluble Non-Cross-Linked Polystyrene and Carbohydrate Scaffold Supports

Abstract: Free radical allylations were studied using (1) soluble non-cross-linked polystyrene supports, (2) carbohydrate scaffolds, and (3) a combination of both synthetic motifs. Allylations on these custom designer supports provide easily purified products, free of tin residues. A D-xylose carbohydrate scaffold bearing a bromoester was used for a diastereoselective allyl tin transfer thermally at 80 degrees C and with Lewis acids. This is the first example of a diastereoselective radical reaction directed by a remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10][11] We have recently demonstrated that triethylborane has the potential to induce the intermolecular radical reactions on solid support. 12,13) Moreover, the employment of triethylborane and its related radical initiator such as diethylzinc at low reaction temperature would facilitate the control of stereochemistry in solidphase reactions.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] We have recently demonstrated that triethylborane has the potential to induce the intermolecular radical reactions on solid support. 12,13) Moreover, the employment of triethylborane and its related radical initiator such as diethylzinc at low reaction temperature would facilitate the control of stereochemistry in solidphase reactions.…”
mentioning
confidence: 99%
“…Therefore the extension of carbon-carbon bond-forming radical reactions to solid-phase reactions would allow further progress in combinatorial organic synthesis. 60,64) In addition to some reports on solid-state radical cyclizations using 2,2Ј-azobisisobutyronitrile (AIBN) or SmI 2 as a radical initiator, 65,66) Sibi's group reported the first studies on the solid-phase intermolecular radical reaction using allyl stannanes and AIBN. 67) To test the viability of triethylborane as a radical initiator on solid support, we first investigated the radical addition to the oxime ether 54 anchored to Wang resin and TentaGel OH resin (Chart 20).…”
Section: Radical Reaction Of Imine Derivatives In Aqueous Mediamentioning
confidence: 99%
“…[2] Although enantiomerically pure compounds [3] are of major interest for the pharmaceutical industry only few stereoselective syntheses on the solid-phase have been reported so far. Besides polymer-bound chiral ligands and catalysts [4] some immobilized chiral auxiliaries and their application in aldol condensations, [5] conjugate additions, [6] 1,3-dipolar cycloadditions, [7] or radical allylations [8] have been described.…”
Section: Gernot Zech and Horst Kunz*mentioning
confidence: 99%